Building relational peace: police-community relations in post-accord Colombia - Nilsson, Manuela (Policing and society, 2023)
As an important pillar of building sustainable peace after protracted violent conflict, security sector reform (SSR) has the objective to prepare state security actors, who often have been active conflict participants, for work within the frameworks of democracy, adherence to human and civil rights, and civilian rule. A major component of SSR is the re-training and re-education of local police to improve their relationship with the local communities. This relationship has often been severely strained by human rights abuses committed by police against community members during the conflict, and it continues to be put to the test in fragile post-accord environments by persisting high levels of violence. However, research on how to improve that relationship, particularly from a bottom-up perspective, remains scarce. This study analyses the dynamics of the relationship between the police and communities in the transition period from war to peace in Colombia, a country tormented by continued violence even after the signing of the 2016 peace agreement that was to set an end to the country’s decades of internal conflict. Based on semi-structured interviews conducted during the fall of 2019, it applies the theoretical lens of the relational peace framework that approaches peace in terms of relationships between different sets of interdependent actors. The findings indicate that the relationship between the communities and the police has not reached satisfactory levels of relational peace, suggesting a set-back in security-related peacebuilding. The paper concludes with recommendations, including from interviewees, on how to improve that relationship.